CROSS-CULTURAL ADAPTATION HELPS ATTRACT AND SUSTAIN INTERNATIONAL STUDENTS - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
GEORGE TOWN, PENANG, 7 April 2016 Crosscultural adaptation is one of the important issues in promoting higher education and attracting international students to enroll in educational institutions in Malaysia.